2008
DOI: 10.1098/rstb.2008.0089
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms underlying the vulnerability to develop compulsive drug-seeking habits and addiction

Abstract: We hypothesize that drug addiction can be viewed as the endpoint of a series of transitions from initial voluntary drug use through the loss of control over this behaviour, such that it becomes habitual and ultimately compulsive. We describe evidence that the switch from controlled to compulsive drug seeking represents a transition at the neural level from prefrontal cortical to striatal control over drugseeking and drug-taking behaviours as well as a progression from ventral to more dorsal domains of the stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
670
1
14

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 882 publications
(709 citation statements)
references
References 93 publications
(146 reference statements)
24
670
1
14
Order By: Relevance
“…Our results, obtained after 13 weeks of nicotine administration, are consistent with previous reports of elevated Met-enkephalin in the striatum following nicotine treatment for periods of 2 weeks, which was measured using immunoassay (15). These results parallel the persistent activation of the DS during long term nicotine exposure or the preoccupation/craving stage of drug dependence (5,45), and the results further support a close functional link between dopamine and enkephalin systems, which are both under the regulation of nicotine (46). Enhancements of the remaining three PENK peptides have not been previously reported and suggest a broader involvement of the PENK pathway than has not been previously uncovered using immunoassay.…”
Section: Table I Changed Prohormone-derived Peptides and Unchanged Knsupporting
confidence: 91%
“…Our results, obtained after 13 weeks of nicotine administration, are consistent with previous reports of elevated Met-enkephalin in the striatum following nicotine treatment for periods of 2 weeks, which was measured using immunoassay (15). These results parallel the persistent activation of the DS during long term nicotine exposure or the preoccupation/craving stage of drug dependence (5,45), and the results further support a close functional link between dopamine and enkephalin systems, which are both under the regulation of nicotine (46). Enhancements of the remaining three PENK peptides have not been previously reported and suggest a broader involvement of the PENK pathway than has not been previously uncovered using immunoassay.…”
Section: Table I Changed Prohormone-derived Peptides and Unchanged Knsupporting
confidence: 91%
“…Although we have demonstrated that phasic dopamine release does indeed develop at a later stage of drug use in the DLS than in the VMS, the training regimen used typically is not sufficient to produce compulsive responding or the significant escalation of drug intake that emerges following extended or long-access training in drug self-administration (31,32). Thus, our data demonstrate that the engagement of DLS dopamine, which is thought to be linked closely to stimulus-response processing (13), is not sufficient to account for the loss of control over drug intake characteristic of addiction, underlining the important dissociation between the habitual and compulsive stages of drug taking and their neural substrates (33). In fact, the behavioral measure that most closely correlated with the emergence of phasic dopamine release in the DLS was the efficiency of response, that is, the number of active nose-poke responses as a proportion of the total number of responses (including time-out responses and responses in the inactive port).…”
Section: Dopamine Signaling In the Sensorimotor Striatum Emerges Beforementioning
confidence: 75%
“…Together with our study, these findings underline the functional significance of the network interaction between the VMS and the DLS in drugrelated behavior. Specifically, they indicate that this circuit is used for multiple, related processes in the procurement of drugs, both in prioritization of drug-taking behavior and the exploitation of a drug environment in animals with a moderate drug history (present study) and in energizing and driving drug-seeking behavior in an environment where the drug is not readily available in animals with an extended drug-taking history (33). Therefore, the hierarchical recruitment of striatal subregions for dopaminemediated control of behavior may signify an overarching organizing principle throughout the stages of drug use to enable representation of drug cues in DLS.…”
Section: Dopamine Signaling In the Sensorimotor Striatum Emerges Beforementioning
confidence: 84%
“…Only a proportion of individuals develop drug addiction after using drugs repeatedly (Everitt et al, 2008). Ample evidence from clinical studies show that stress during the perinatal period (prenatal and early postnatal) in the form of mental or physical stress could lead to increased addiction risk during adulthood (Charmandari et al, 2003).…”
Section: Introductionmentioning
confidence: 99%